A Typology Proposition of Effective Visual Programming Practices - Parent, Simon (Canadian Journal of Learning and Technology, 2022)
This article presents the results of a multiple-case study conducted with 18 primary school students in Quebec, Canada. The objective of this study was to propose a typology of effective visual programming practices of primary school students. In addition to offering a detailed portrait of the practices mobilized by the students in this research, we present a typology of visual programming tasks for primary school students based on the literature and on empirical data from the use of a pedagogical scenario which allows students to mobilize their skills by programming a humanoid robot called NAO. This proposal for a comprehensive and adapted typology offers a significant pedagogical potential, whether for the design of pedagogical scenarios mobilizing visual programming in primary education, or for the development of textbooks or pedagogical guides for primary school students or teachers.